Telemedicine Practices on Doctors' Responsibilities in Health Service Facilities (Fasyankes) from Civil Law: A Normative Juridical Study - Komang Arya Adiputra; I Wayan Gede Artawan Eka Putra (Indonesian Journal of Global Health Research, 2026)
The development of information technology has driven the transformation of healthcare services through telemedicine, offering ease of access, time efficiency, and expanded reach of medical services. However, the implementation of telemedicine also raises various legal issues, particularly regarding the civil liability of physicians and legal protection for patients. The differences in the characteristics of conventional medical services and digital-based healthcare services require clear legal regulations to create legal certainty and justice for all parties. This study aims to analyze the form of legal relations between doctors and patients in telemedicine services and examine the basis for civil liability of physicians for losses experienced by patients. The research method used is normative legal research with a statutory, conceptual, and comparative approach. The legal materials analyzed include laws and regulations in the fields of health and telemedicine, civil law doctrine, and the latest scientific articles indexed by Scopus and Web of Science. The results of the study indicate that the legal relationship in telemedicine remains based on a therapeutic agreement that gives rise to the rights and obligations of the parties. Physicians can be held civilly liable for both breach of contract and unlawful acts if they are proven to have violated professional standards, the principle of prudence, or the rights of patients. However, this study also found regulatory gaps and disharmony, which have weakened legal certainty and legal protection mechanisms for patients.  This study's conclusions emphasize the need to strengthen and harmonize telemedicine regulations to ensure legal protection for patients and provide legal certainty for doctors in conducting digital-based medical practices.